An exceedingly rare adrenal collision tumor: adrenal adenoma-metastatic breast cancer-myelolipoma - Dongyan Liu; Sahayini A. Kumar (Greater Baltimore Medical Center, 2017)
Adrenal collision tumors (ACTs), in which distinct tumors coexist without histological intermingling in the same adrenal gland, are rare and their actual prevalence is unknown. ACTs commonly consist of adrenal cortical adenoma, myelolipoma, or metastatic malignant tumor. We report a 58-year-old woman with a past history of breast cancer, who presented with a 1 month history of fevers, chills, and abdominal fullness. The physical examination and the laboratory data including endocrine studies were unremarkable. Computed tomography of the abdomen showed a right adrenal gland mass, and a laparoscopic right adrenalectomy was performed. Histological and immunohistochemical examinations revealed three distinct tumors: an adrenal cortical adenoma, a myelolipoma, and metastatic breast tumors. Breast cancer metastases are rare in the adrenal gland and exist as ACTs only in exceptionally rare cases. To our knowledge, this is the first reported case of coexisting metastatic breast tumors, adrenal adenoma, and myelolipoma in the same adrenal gland.